Does Monetary Policy Regime Determine the Nature of the Money Supply?: Evidence from Seven Countries in the Asia-Pacific Region - Hee-Yul Chai; Sang B. Hahn (East Asian Economic Review (EAER), 2018)
This paper tests empirically the causal relationship between bank loans and the monetary base before and after the adoption of inflation targeting in seven Asia-Pacific countries using Toda-Yamamoto Granger non causality test and the bootstrap test for causality. The most striking finding is that the bank loans Granger cause the monetary base during the inflation targeting period in all the countries, except Japan, which was under the influence of the quantitative easing, whereas the causality appeared diverse before the inflation targeting regime. This result implies the need for the policy makers to take the endogenous nature of the money supply into account in the modern economy.
Keywords: E44; E51; E52; 330; Endogenous Money Supply; Money Multiplier; Monetary Policy Regime; Granger Causality; Bootstrap Test